Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Discours sur le corps et la sexualité des femmes : analyse de la réception médiatique du mouvement Femen - Tremblay, Stéphanie (Université du Québec à Montréal, 2022)
Le mouvement Femen est un groupe féministe international qui manifeste seins nus. Au Québec comme un peu partout dans le monde, les Femen attirent l’attention des médias. Le discours médiatique entourant ce mouvement constitue donc un objet d’étude intéressant afin d’explorer la question plus large du rapport au corps et à la sexualité des femmes. Dans le cadre de ce projet, une analyse critique de discours a été menée sur 214 textes issus de cinq groupes de quotidiens québécois francophones. Alors qu’on tend à penser que l’égalité entre les sexes est atteinte au Québec, le discours médiatique québécois entourant le mouvement Femen révèle que le corps, la nudité et la sexualité des femmes font l’objet d’un contrôle social en plus d’un regard patriarcal, colonialiste et hétéronormé. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femen, agentivité sexuelle, slut-shaming, discours médiatique, féminisme, corps, nudité
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité sexuelle; amériques; analyse de discours; approches et analyses; corps; discipline; hétérosexisme; intersectionnalité; militance; mémoires/thèses; nudité; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; système colonial; systèmes d'oppressions; thématiques; violences